2019
DOI: 10.1002/wsb.970
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Experimental tests to improve efficacy of fladry for nonlethal management of coyotes

Abstract: Coyotes (Canis latrans) are the top predator of livestock in the contiguous United States. Developing more effective nonlethal tools to prevent coyote depredation will facilitate coexistence between livestock producers and coyotes. Fladry is a nonlethal deterrent designed to defend livestock by creating a visual barrier to wolves (C. lupus). Fladry may also be effective with coyotes, but large gap spacing between flags may reduce its efficacy. To address this issue, we performed 2 experiments on captive coyote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…These approaches may have important consequences for evolutionary change in cities. (Young, Draper, et al, 2019;Young, Hammill, et al, 2019) and rodenticides are now restricted in some jurisdictions (Quinn et al, 2019). Incorporating evolutionary concepts in such management decisions will help inform successful mitigation strategies.…”
Section: Box 1 Case Studies: Coyotes Versus Brown Ratsmentioning
confidence: 99%
“…These approaches may have important consequences for evolutionary change in cities. (Young, Draper, et al, 2019;Young, Hammill, et al, 2019) and rodenticides are now restricted in some jurisdictions (Quinn et al, 2019). Incorporating evolutionary concepts in such management decisions will help inform successful mitigation strategies.…”
Section: Box 1 Case Studies: Coyotes Versus Brown Ratsmentioning
confidence: 99%
“…It is essential to understand how these cues interact with other aspects of behavior and how salience of cues varies within and across target species to achieve maximum efficacy. In the case of fladry, small adjustments in the spacing of flags hung from ropes are required to effectively deter coyotes as compared to wolves (Young, Draper, & Breck, 2019), and subordinate coyotes are more neophobic in response to fladry than dominant coyotes (Mettler & Shivik, 2007).…”
Section: Instilling Fear To Mitigate Human-wildlife Conflictmentioning
confidence: 99%
“…We modified standard turbo fladry to a narrower flag spacing of 27.9 cm (Young et al ., 2019 a ) and tested its effectiveness at excluding coyotes from areas within fladry exclosures on each treatment colony (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Although coyotes Canis latrans have similar neophobic responses to that of wolves (Mettler & Shivik, 2007), the horizontal spacing of flags on commercial fladry and turbo fladry is likely unsuitable for smaller‐sized coyotes (Davidson‐Nelson & Gehring, 2010). As a result, a recent captive study used the ratio of wolf body width to the horizontal spacing between fladry flags and narrowed the spacing of flags for use with coyotes (Young, Draper & Breck, 2019 a ). The study found that modified coyote fladry, when compared with commercial fladry, nearly doubled the duration of effectiveness when used with coyotes (Young et al ., 2019 a ); however, coyote fladry has yet to be tested in a field setting.…”
Section: Introductionmentioning
confidence: 99%